2018
DOI: 10.1021/acs.jpcb.8b07112
|View full text |Cite
|
Sign up to set email alerts
|

Decorrelating Kinetic and Relaxation Parameters in Exchange Saturation Transfer NMR: A Case Study of N-Terminal Huntingtin Peptides Binding to Unilamellar Lipid Vesicles

Abstract: Dark state exchange saturation transfer (DEST) and lifetime line-broadening (Δ R, the difference in the measured transverse relaxation rates for the observable species in the presence and absence of exchange with a species characterized by very large intrinsic transverse relaxation rates) have proven to be powerful NMR tools for studying exchange phenomena between a NMR visible species and a high-molecular weight, "dark", NMR invisible state. However, in the exchange regime, where the transverse spin relaxatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
25
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(26 citation statements)
references
References 19 publications
(88 reference statements)
1
25
0
Order By: Relevance
“…The N-terminal 17-residue sequence has been demonstrated to adopt a largely helical conformation when being membranes-associated (41,42,77,78), when part of a htt17-polyQ fiber (45,46,79) or in aggregation intermediates (51,73). Here we have shown that the membrane interactions of the htt17 flanking region of the polyQ domain promotes the aggregation process of huntingtin exon 1.…”
Section: Discussionmentioning
confidence: 61%
See 3 more Smart Citations
“…The N-terminal 17-residue sequence has been demonstrated to adopt a largely helical conformation when being membranes-associated (41,42,77,78), when part of a htt17-polyQ fiber (45,46,79) or in aggregation intermediates (51,73). Here we have shown that the membrane interactions of the htt17 flanking region of the polyQ domain promotes the aggregation process of huntingtin exon 1.…”
Section: Discussionmentioning
confidence: 61%
“…Recent structural investigations reveal a highly dynamic behaviour of htt17 and the subsequent polyQ domain where htt17 association (23), its interactions with the membrane (39)(40)(41)(42)(43) or with other polypeptide domains are associated with random coilhelix structural transitions (44,45). Interestingly, the htt17 and the polyQ domains mutually influence each other and their conformational properties are coupled (46,47).…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…For rapidly exchanging nanoparticle surfaces, conditions are chosen so that only a small fraction of the total protein concentration interacts with the nanoparticle. Then, relaxation behavior and other properties are used to study the bound state, offering the possibility of performing numerous experiments that can address a variety of features in studying NP‐protein interactions.…”
Section: Solution Nmr Approaches For Nanoparticle Studiesmentioning
confidence: 99%